Acute Stroke With Large Vessel Occlusion and Minor Clinical Deficits: Prognostic Factors and Therapeutic Implications - Volbers, Bastian; Gröger, Rebecca; Engelhorn, Tobias; Marsch, Armin; Macha, Kosmas; Schwab, Stefan; Dörfler, Arnd; Lang, Stefan; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background and Purpose: The optimal acute management of patients with large vessel occlusion (LVO) and minor clinical deficits on admission (NIHSS ≤4) remains to be elucidated. Aim of the present study was to investigate prognostic factors and the therapeutic management of those patients. Methods: In this retrospective cohort study, we investigated 1) all patients with acute ischemic stroke due to a LVO who underwent mechanical thrombectomy (MT) and 2) all patients with minor clinical deficits (NIHSS <=4) on admission due to a LVO between 01/2013 and 12/2016 at the University Medical Center Erlangen. We dichotomized management of patients with minor deficits treated with mechanical thrombectomy for analysis according to “immediate mechanical thrombectomy (IT)” and “initial medical management with rescue-intervention (MM) in case of secondary deterioration”. Primary endpoints were in-hospital-mortality and functional outcome on day 90 (dichotomized modified Rankin Scale 0-2: favorable, 3-6: poor). Results: 223 patients (83% with anterior circulation stroke, thirteen (6%) with minor deficits) treated with MT and 88 patients with minor deficits due to LVO (thirteen (15%) treated with MT) were included. Secondary deterioration (n=19) was independently associated with poor outcome in patients with minor deficits and LVO (OR 0.060, 95% CI 0.013-0.280), which in turn was associated with the occlusion site (especially M1-occlusion: 11 (58%) vs. 3 (4%) in patients without secondary deterioration, p<0.0001). IT (n=8) was associated with a lower intra-hospital mortality compared to MM (n=5; 13 vs. 80%; OR 0.036 (95% CI 0.002-0.741)). Seven of eight patients with IT survived until discharge with 29% showing a favorable functional outcome on day 90. Conclusions: Secondary deterioration is associated with poor outcome in patients with LVO and minor deficits, which in turn was associated with occlusion site. Future RCTs should assess, whether selected patients depending on occlusion site and associated characteristics may benefit from MT. Clinical Trial Registration: N/A